Characterizing the setting of cement when mixed with cork, blue gum, or maritime pine, grown in Portugal - II: X-ray diffraction and differential thermal analyzes (JOURNAL OF WOOD SCIENCE, 2006)
It is already known by the scientific and industrial communities that lignocellulosic substrates are, to a certain extent, inhibitors of the hydration reaction of cement. The extent to which and how they influence such reactions is still a matter of debate. Several techniques, such as calorimetry, i.e., the measurement of the heat evolved or obtaining temperature profiles during the hydration, the determination of extractive contents of lignocellulosic substrates and their relation with the characteristics of the hydration curves, or even testing of the mechanical properties of the wood-cement composites, have been used in previous research. This study complements past research using two techniques that have been used in the analysis of cement hydration but are not usually applied to lignocellulose-cement mixes, namely X-ray diffraction (XRD) and differential thermal analysis (DTA). The raw materials for this study were three lignocellulosic materials of Portuguese origin: cork (the bark of Quercus suber L.), blue gum (Eucalyptus globulus Labill.), and maritime pine (Pinus pinaster Ait); and Portland cement. The two techniques allowed tracking of the evolution of the main cement constituents during hydration. It was found that all the lignocellulosic substrates had detrimental effects on cement hydration. The blue gum exhibited the fastest hydration kinetics in the initial stage of reaction, but was then overtaken by cork, which at the end gave the highest hydration conversion amongst the three lignocellulosic substrates. Although pine caused the slowest initial hydration kinetics, with the passage of time its effect approached that of blue gum. At the end of the hydration period, specimens containing either species had similar quantities of hydration reaction products. The DTA and XRD results were consistent and are in good agreement with the temperature profiles and compatibility indexes reported in a previous work.

Characterizing the setting of cement when mixed with cork, blue gum, or maritime pine, grown in Portugal - II: X-ray diffraction and differential thermal analyzes - Pereira, Catarina; Jorge, Fernando Caldeira; Irle, Mark; Ferreira, Jose Maria (JOURNAL OF WOOD SCIENCE, 2006)
It is already known by the scientific and industrial communities that lignocellulosic substrates are, to a certain extent, inhibitors of the hydration reaction of cement. The extent to which and how they influence such reactions is still a matter of debate. Several techniques, such as calorimetry, i.e., the measurement of the heat evolved or obtaining temperature profiles during the hydration, the determination of extractive contents of lignocellulosic substrates and their relation with the characteristics of the hydration curves, or even testing of the mechanical properties of the wood-cement composites, have been used in previous research. This study complements past research using two techniques that have been used in the analysis of cement hydration but are not usually applied to lignocellulose-cement mixes, namely X-ray diffraction (XRD) and differential thermal analysis (DTA). The raw materials for this study were three lignocellulosic materials of Portuguese origin: cork (the bark of Quercus suber L.), blue gum (Eucalyptus globulus Labill.), and maritime pine (Pinus pinaster Ait); and Portland cement. The two techniques allowed tracking of the evolution of the main cement constituents during hydration. It was found that all the lignocellulosic substrates had detrimental effects on cement hydration. The blue gum exhibited the fastest hydration kinetics in the initial stage of reaction, but was then overtaken by cork, which at the end gave the highest hydration conversion amongst the three lignocellulosic substrates. Although pine caused the slowest initial hydration kinetics, with the passage of time its effect approached that of blue gum. At the end of the hydration period, specimens containing either species had similar quantities of hydration reaction products. The DTA and XRD results were consistent and are in good agreement with the temperature profiles and compatibility indexes reported in a previous work.
The following values have no corresponding Zotero field: pub-location: 3-3-13, HONGO, BUNKYO-KU, TOKYO, 113-0033, JAPAN publisher: SPRINGER TOKYO
Keywords: cement; Cork; differential thermal analysis; Wood; X-ray diffraction